2022
DOI: 10.1088/1748-9326/ac6e77
|View full text |Cite
|
Sign up to set email alerts
|

Palm oil’s contribution to the United Nations sustainable development goals: outcomes of a review of socio-economic aspects

Abstract: Palm oil is at the same time the world’s most used vegetable oil and the most criticized for its environmental impacts due to the observed reduction in tropical forest areas for its cultivation over the past decades. There is, however, very little discussion on the socio-economic implications associated with the production of palm oil. To contribute to a more informed debate we conducted an in-depth review of the existing literature addressing the various socio-economic aspects of the production of palm oil, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 93 publications
0
11
0
Order By: Relevance
“…According to cooperatives, it was stated that the revitalization of cooperative organizations in rural areas through strategic marketing places is the most important characteristic of partnerships in terms of improving people's living standards and working conditions. Previous research also reported that to increase regional economic growth, it is necessary to develop other sectors that have high potential such as oil palm plantations and the processing industry in line with the Sustainable Development Goals [44][45][46]. The results of previous research by Pramudya et.…”
Section: Factors Affecting the Nuclear Plasma Pattern Partnership In ...mentioning
confidence: 95%
“…According to cooperatives, it was stated that the revitalization of cooperative organizations in rural areas through strategic marketing places is the most important characteristic of partnerships in terms of improving people's living standards and working conditions. Previous research also reported that to increase regional economic growth, it is necessary to develop other sectors that have high potential such as oil palm plantations and the processing industry in line with the Sustainable Development Goals [44][45][46]. The results of previous research by Pramudya et.…”
Section: Factors Affecting the Nuclear Plasma Pattern Partnership In ...mentioning
confidence: 95%
“…Essentially, the government's policy to develop oil palm plantations is a positive thing and is considered to be able to help farmers' economic growth (23,28) so that the positive impacts of this sector can continue to be managed (8). Based on the results of the group query analysis in Figure 2, it is found that each stakeholder has various perceptions of the existing conditions of oil palm plantation management in Riau Province: 22) explains that each actor who plays a role in natural resource management will have different connections and power with one another, whereas actors who have strong connections will be able to determine strategies to improve natural resource governance and apply the process at each level.…”
Section: Existing Condition Of Palm Oil Plantation Management In Riau...mentioning
confidence: 99%
“…From an ecological perspective, oil palm plantations contribute to carbon dioxide and oxygen cycle conservation, land restoration, soil, and water conservation, increasing land biomass and carbon stock, and reducing greenhouse gas emissions/peatland improvement. With this whole paradigm, the Indonesian palm oil industry continues to grow in a sustainable perspective (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been conducted to view the potential of making SDGs as palm oil impact assessment tools, but most are still limited to discussions for more appropriate applications [10,11]. Works of literature regarding palm oil plantations' impacts on the SDGs' realization are still restricted to conceptual discussion and the palm oil sector's possibility to the SDGs [12,13].…”
Section: Introductionmentioning
confidence: 99%